Genome-Wide Analysis of the R2R3-MYB Gene Family in Fragaria × ananassa and Its Function Identification During Anthocyanins Biosynthesis in Pink-Flowered Strawberry - Liu, Jiaxin; Wang, Jian; Wang, Mingqian; Zhao, Jun; Zheng, Yang; Zhang, Tian; Xue, Li; Lei, Jiajun (Frontiers in Plant Science, 2021)
The strawberry (Fragaria × ananassa) is an economically important fruit throughout the world. The large R2R3-MYB gene family participates in a variety of plant functions, including anthocyanin biosynthesis. The present study is the first genome-wide analysis of the MYB gene family in the octoploid strawberry and describes the identification and characterization of the family members using the recently sequenced F. × ananassa genome. Specifically, we aimed to identify the key MYBs involved in petal coloration in the pink-flowered strawberry, which increases its ornamental value. A comprehensive, genome-wide analysis of F. × ananassa R2R3-FaMYBs was performed, investigating gene structures, phylogenic relationships, promoter regions, chromosomal locations, and collinearity. A total of 393 R2R3-FaMYB genes were identified in the F. × ananassa genome and divided into 36 subgroups based on phylogenetic analysis. Most genes with similar functions in the same subgroup exhibited similar exon-intron structures and motif compositions. These R2R3-FaMYBs were unevenly distributed over 28 chromosomes. The expansion of the R2R3-FaMYB gene family in the F. × ananassa genome was found to be caused mainly by segmental duplication. The Ka/Ks analysis indicated that duplicated R2R3-FaMYBs mostly experienced purifying selection and showed limited functional divergence after the duplication events. To elucidate which R2R3-FaMYB genes were associated with anthocyanin biosynthesis in the petals of the pink-flowered strawberry, we compared transcriptional changes in different flower developmental stages using RNA-seq. There were 131 differentially expressed R2R3-FaMYB genes identified in the petals, of which three genes, FaMYB28, FaMYB54, and FaMYB576, appeared likely, based on the phylogenetic analysis, to regulate anthocyanin biosynthesis. The qRT-PCR showed that these three genes were more highly expressed in petals than in other tissues (fruit, leaf, petiole and stolon) and their expressions were higher in red compared to pink and white petals. These results facilitate the clarification on the roles of the R2R3-FaMYB genes in petal coloration in the pink-flowered strawberry. This work provides useful information for further functional analysis on the R2R3-FaMYB gene family in F. × ananassa.